Generation of DNA constructs using the golden GATEway cloning method - Kirchmaier, Stephan; Lust, Katharina; Wittbrodt, Joachim (Synthetic DNA, 2017)
One of the most frequently executed tasks for molecular biologists is the design and generation of complex DNA constructs. Recently, we established the Golden GATEway cloning kit for the fast and efficient generation of transgenesis vectors. This cloning kit allows the modular assembly of DNA fragments in a defined order. The modularity reflects how complex transgenesis constructs are set up. For example, genome modification tools such as the Cre-Lox system utilize small recombination elements that are combined with larger open reading frames and noncoding regulatory DNA. Another example is that proteinogenic genes can be extended with different localisation tags or fluorescent markers. The Golden GATEway cloning kit allows focusing on the design of a transgenesis construct without having to compromise it by so far available cloning strategies. Here, we provide a step-by-step introduction on how to use the Golden GATEway cloning kit.